Peranan Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Pendidikan Melalui Aspek Kinerja Guru di SDN Labuy Kabupaten Aceh Besar - Mawardi, Mawardi; Novita, Rita; Zahraini , Zahraini (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to determine the leadership of the principal in carrying out his function of improving school quality through aspects of teacher performance, the role of the principal in improving school quality and to find out the obstacles and obstacles of the principal in improving the quality of education related to aspects of teacher performance at SDN Labuy Aceh Besar. This research uses a qualitative approach with a case study type. Data collection techniques through observation and unstructured interviews. Data is analyzed through qualitative data analysis consisting of data reduction, data presentation, and conclusion drawing. The results of research in the field show that the leadership of the principal in carrying out his function improves the quality of the school through aspects of teacher performance at SDN Labuy Aceh Besar. The role of the principal in improving school quality through aspects of teacher performance at SDN Labuy Aceh Besar is, as a leader, manager, educator, supervisor, administrator, innovator, and motivator. The obstacles and obstacles experienced by school principals in improving the quality of education related to aspects of teacher performance at SDN Labuy Aceh Besar are still lack of teacher discipline, lack of supporting funds to improve school quality and limited school facilities available.